A(n) = - 4+ (n - 1)(6)

find the third, fourth and, eleventh terms of the sequence described by the rule

A(3)=____

A(4)=____

A(11)=____

I WILL GIVE BRAINLEST ❤️❤️​

Respuesta :

Answer:

answers in steps

Step-by-step explanation:

if A(n) = - 4+ (n - 1)(6) means A(n) = - 4+ (n - 1) x 6

A(3) = - 4+ (3 - 1) x 6 = 8

A(4) = - 4+ (4 - 1) x 6 = 14

A(11) = - 4+ (11 - 1) x 6 = 56

if A(n) = - 4+ (n - 1)(6) means A(n) = - 4+ (n - 1)⁶

A(3) = - 4+ (3 - 1)⁶ = - 4 + 64 = 60

A(4) = - 4+ (4 - 1)⁶ = - 4 + 6561 = 6557

A(11) = - 4+ (11 - 1)⁶ = - 4 + 1000000 = 999996

ACCESS MORE